Plant water relations and edaphoclimatic conditions affecting acorn production in a holm oak (Quercus ilex L. ssp. ballota) open woodland (Agroforestry Systems, 2009)
Acorn production patterns and the annual evolution of water relations parameters of Quercus ilex ssp. ballota (Desf.) Samp. in a dehesa (an open woodland forest) subject to various soil treatments (ploughing, ploughing? sowing, control) were studied in southwest Spain from June 2006 to December 2008. The effects of soil water holding capacity and effective soil depth on soil and plant water status and acorn production were also investigated. Water parameters showed signiÞcant differences between the ploughing treatment and the control, and there were also signiÞcant temporal differences. Xylem water potential ranged from- 3.4 ± 0.1 to - 0.7 ± 0.2 MPa, and cuticular transpiration was 62.4Ð 192.9 mmol H2O kg - 1 s - 1 . Acorn production did not differ signiÞcantly according to soil treatment, and showed large intra-speciÞc variability. Individual values ranged from 0 to 1,220 g m - 2 (fresh weight). Positive relationships were found between xylem water potential, cuticular transpiration and relative water content measured at midsummer, and acorn production during the three studied years. These results suggest that climatic conditions and soil water availability have a strong inßuence on plant water status, and therefore on acorn development during summer. The results also reßect the ability of this species to adapt to the Mediterranean climate by preserving water during dry periods, which to a large extent can be attributed to stomatal closure at high relative water content levels, an

Influence of pruning and the climatic conditions on acorn production in holm oak (Quercus ilex L.) dehesas in SW Spain (Annals of Forest Science, 2008)
Acorn production by Quercus ilex L. ssp. ballota (Desf.) Samp. in SW Spain was assessed, and variations between years and the inﬂuence of pruning on it were examined. To this end, an experimental study was conducted at two diﬀerent sites (Calañas and San Bartolomé, in the province of Huelva) where trees were subjected to traditional (light, moderate or heavy) pruning and also to a new (crown-regeneration) pruning method. Acorn yield was quantiﬁed over a period of 5 years in the Calañas plot and 4 in the San Bartolomé plot, and found to average at 95.61 ± 0.76 g DM/m2 , which is equivalent to 6.5 ± 0.05 kg DM/tree; however, yield ﬁgures varied markedly between years depending on the particular climatic conditions. The average acorn production was correlated with the water potential in mid summer (end of July); the annual, spring and autumn rainfall; and the actual evapotranspiration for the period from September (previous year) to August. No signiﬁcant diﬀerences in acorn production between traditional pruning intensities were detected; in fact, there were only hints that heavy pruning might result in decreased acorn yields. The new pruning method used, crown-regeneration, seems promising with a view to increasing acorn yield; however, it should be tested on larger sample sizes before any ﬁnal conclusions can be drawn in this respect. Based on the results, the present health status of holm oaks in southwestern Spain (a result of sustained decline) and the low value of ﬁrewood – which used to be a very important source of income from pruning a few decades ago –, the authors recommend reducing the frequency and intensity of pruning in the dehesas of the study area.

EVOLUCIÓN TEMPORAL DEL GRADO DE ENDURECIMIENTO DE PLANTAS DE VIVERO DE 4 ESPECIES FORESTALES ESPAÑOLAS CULTIVADAS EN LOCALIDADES CON CONDICIONES CLIMÁTICAS DISTINTAS (IV Congreso Forestal Español, 2005)
Desde principio del otoño hasta principio de primavera se estudió la evolución de algunos caracteres morfo-fisiológicos indicadores de la calidad de las plantas de vivero destinadas a repoblación forestal (altura, diámetro, distribución de biomasa, nutrición mineral, capacidad de regeneración de raíces y resistencia al frío). Las especies ensayadas fueron Quercus suber, Q. ilex (de dos regiones de procedencia, 11e y 15a), Pistacia lentiscus y Olea europaea var. sylvestris. Todas ellas eran de una savia, procedentes de semillas germinadas en la primavera anterior, crecidas en el mismo tipo de envase (300 cm3) y con el mismo substrato pero cultivadas en dos viveros de localización y características climáticas diferentes. En cuanto al patrón de evolución temporal de los parámetros medidos, se advirtió una alta correlación con la temperatura ambiente, siendo el vivero de clima con estaciones más marcadas el que alcanzó con anterioridad su grado máximo de resistencia al frío y el que retrasó la salida de la dormición durante la época invierno-primavera. Indudablemente, las distintas especies se diferenciaron en su patrón de evolución y en el grado de resistencia al frío conseguido, debiendo resaltar las diferencias encontradas entre las dos procedencias de encina, siendo la de clima con estaciones más extremas (15a) la que en todo momento presentó un mayor grado de resistencia al frío. También se encontró un alto grado de correspondencia entre el contenido en K y la resistencia al frío o el contenido en N y P con la capacidad de regeneración de raíces. Las cuatro especies necesitaron acumular, al menos, 350 h (< 8 ºC) para conseguir un grado apreciable de resistencia al frío, alcanzándose el máximo resistencia entre 700 y 800 h